2020
DOI: 10.21003/ea.v183-09
|View full text |Cite
|
Sign up to set email alerts
|

Accrual accounting and public finance reforms in Hungary: the study of application in the public sector

Abstract: Introduction. The increasing measurability of performances in the public sector in the countries of the post-soviet region, including Hungary, has come to the limelight in recent decades. Accrual accounting, adopted in Hungary in 2014 on the recommendation of the European Union, provides decision-makers with reliable information and simultaneously improves transparency in spending. Purpose and Methodology. This study focuses on the impacts and synergies of the parallel comprehensive reforms in the public fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…ing is widely disputed (e.g. Tóth, 2020; Molnár, Hegedűs, 2017), the author of this paper sees its changes, overall, as a positive, forward-looking shift (Lentner, 2020). compare the opinions with the original objectives: Bathó, 2012. functioning of the selected auditors in the category of external audit.…”
Section: Discussionmentioning
confidence: 85%
“…ing is widely disputed (e.g. Tóth, 2020; Molnár, Hegedűs, 2017), the author of this paper sees its changes, overall, as a positive, forward-looking shift (Lentner, 2020). compare the opinions with the original objectives: Bathó, 2012. functioning of the selected auditors in the category of external audit.…”
Section: Discussionmentioning
confidence: 85%
“…Current research in different countries confirm the relationship between the performance of the SAIs and the maintenance of good governance (Meiss et al, 2017;Milojević et al, 2018;Nevidomyi & Kanonishena-Kovalenko, 2019;Lentner et al, 2020;Bardash & Osadcha, 2020;Çeku, 2021;Bostan et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 83%
“…As noted by Lentner et al (2020), the most significant disadvantage of the cash approach is that it is impossible to accurately determine the financial position of the particular budgetary organization, as well as to adequately establish the total amount of actual expenses.…”
Section: Content Analysis Of the Reports Of Thementioning
confidence: 99%
“…The literature shows that local governments have largely perceived consolidated financial statements as a tool that they can use to provide a clearer picture of their efficiency and effectiveness in the use of public resources while improving their transparency and raising the public’s perception of their organizational conduct (Santis et al , 2019). In European countries such as Portugal (Gomes et al , 2015), Estonia (Haldma and Kenk, 2014), Hungary (Lentner et al , 2020) and Malta (Jones and Caruana, 2014) pressure from the central and local governments is seen as a stimulus in accounting reform through the adoption of the business accounting model to improve the economy and the efficiency and effectiveness of government operations.…”
Section: Resultsmentioning
confidence: 99%
“…Limited financial resources. In developed countries, the processes to implement accounting reforms are very costly and involve many expenses, including staff training, hardware and software acquisition (Klimavi cien_ e and Mykolaitien_ e, 2007; Lentner et al, 2020;Nakmahachalasint and Narktabtee, 2019;Ridder et al, 2005). For example, in a recent study about the constraints for the implementation of an accrual basis in public sector accounting in Croatia, Hladika (2022) found that public sector managers rated financial resources as the greatest constraint.…”
Section: Public Accounting Reformmentioning
confidence: 99%